"Girls Are as Good as Boys at Math" Implies That Boys Are Probably Better: A Study of Expressions of Gender Equality. (28th June 2018) - Chestnut, Eleanor K.; Markman, Ellen M.
Abstract: Although "Girls are as good as boys at math" explicitly expresses equality, we predict it could nevertheless suggest that boys have more raw talent. In statements with this subject‐complement structure, the item in the complement position serves as the reference point and is thus considered more typical and prominent. This explains why "Tents are like houses, " for instance, sounds better than "Houses are like tents"—people generally think of houses as more typical. For domains about ability, the reference point should be the item that is typically more skilled. We further propose that the reference point should be naturally more skilled. In two experiments, we presented adults with summaries of actual scientific evidence for gender equality in math (Experiment 1) or verbal ability (Experiment 2), but we manipulated whether the reference point in the statements of equality in the summaries (e.g., "Boys' verbal ability is as good as girls'") was girls or boys. As predicted, adults attributed more natural ability to each gender when it was in the complement rather than subject position. Yet, in Experiment 3, we found that when explicitly asked, participants judged that such sentences were not biased in favor of either gender, indicating that subject‐complement statements must be transmitting this bias in a subtle way. Thus, statements such as "Girls are as good as boys at math" can actually backfire and perpetuate gender stereotypes about natural ability.